What do ultrasound vocalizations really mean in rats with different origins of pain? - Yang Yu; Chun-Li Li; Rui Du; Xiao-Liang Wang; Jun Chen (PAIN Reports)
Abstract. Objectives:. This study is to assess how 22 kHz and 50 kHz spontaneous ultrasound vocalization (USV) calls would be affected by different origins of pain so as to validate the use of USV in pain studies. Methods:. Five well-established rat models of pain were used to evaluate various parameters of spontaneous 22 kHz and 50 kHz calls in adult male rats in terms of both acute and chronic or inflammatory and neuropathic or somatic and visceral origins. The effects of local lidocaine blockade of the injection site and intraperitoneal administration of antidepressant (amitriptyline) and anticonvulsant (gabapentin) were examined as well in typical inflammatory and neuropathic pain models, respectively. Results:. The major new gains were as follows: (1) naive rats staying alone and engaging dyadic social interaction with a naive or a conspecific in pain emitted similar power and amounts of both 22 kHz and 50 kHz spontaneous USV calls; however, rats suffering from various origins of pain emitted significantly less USV calls of both 22 kHz and 50 kHz in terms of both number and time. (2) Local blockade of the injury sites of inflammatory pain could reverse the impaired emission of both 22 kHz and 50 kHz spontaneous calls, so did the treatment of the rats with neuropathic pain by amitriptyline and gabapentin. Conclusions:. Emissions of both 22 kHz and 50 kHz spontaneous calls were impaired by acute and chronic pain conditions regardless of inflammatory and neuropathic or somatic and visceral origins.